Australian money advice and debt management system - Seajin Kim (United Nations Research Institute for Social Development (UNRISD), 2023)
In Australia, financial hardship caused by over-indebtedness is no longer only experienced by the most vulnerable social group but is now prevalent among the general population. This scoping paper analyses the money advice and debt management system in Australia with emphasis on their effectiveness. First, money advice is divided into debt counselling and financial advice services. Public organizations and government departments responsible for money advice are assessed in terms of their role, approach, brief history, interrelationship and impact on people. Second, debt management options and responsible institutions are investigated in detail. Less is known about the impacts of different debt management options since little research is currently available. Therefore, this scoping paper concludes that while preventative, curative and rehabilitative measures are available for Australian debtors, interaction among stakeholders within the system must expand together along with the publication of an evaluation of the country's financial service landscape.
Keywords: 330; Schuldenmanagement; Verbraucherberatung; Anlageberatung; Private Verschuldung; Insolvenz; Australien